2019
DOI: 10.1016/j.triboint.2019.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of WC on third body behaviour during fretting of cold-sprayed Cu MoS2WC composites

Abstract: Fretting wear behaviour of cold-sprayed Cu-MoS2 and Cu-MoS2-WC composites rubbing against AISI 440C steel was studied under gross slip regime. Third body rheology during running-in and steady state was expressed using tribological circuit according to morphology observations on wear scars and transfer materials on the counterfaces. The velocity accommodation mechanisms (VAMs) were therefore identified. Presence of WC particles boosted generation and ejection of large wear particles during running-in and early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Subsequently, research on the influence of WC particles on the third bodies and wear resistance was conducted by changing the concentrations of Cu-MoS 2 and WC powders in the experiments, which yielded similar results. The presence of WC particles contributes to the formation of a continuous tribological transition structure (TTS) layer and a transfer film during the contact process, which makes the third-body flow smaller and more stable, so as to significantly improve the wear resistance of the Cu-MoS 2 -WC coating [55].…”
Section: Cold-sprayed Cu-based Self-lubricating Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, research on the influence of WC particles on the third bodies and wear resistance was conducted by changing the concentrations of Cu-MoS 2 and WC powders in the experiments, which yielded similar results. The presence of WC particles contributes to the formation of a continuous tribological transition structure (TTS) layer and a transfer film during the contact process, which makes the third-body flow smaller and more stable, so as to significantly improve the wear resistance of the Cu-MoS 2 -WC coating [55].…”
Section: Cold-sprayed Cu-based Self-lubricating Coatingsmentioning
confidence: 99%
“…Subsequently, research on the influence of WC particles on the third bodies and wear resistance was conducted by changing the concentrations of Cu-MoS2 and WC powders in the experiments, which yielded similar results. The presence of WC particles contributes to the formation of a continuous tribological transition structure (TTS) layer and a transfer film during the contact process, which makes the third-body flow smaller and more stable, so as to significantly improve the wear resistance of the Cu-MoS2-WC coating [55]. In the preparation of Ni-hexagonal boron nitride (hBN) self-lubricating coatings by mechanical grinding and CS, Smid et al [100] found that the self-lubricating and wear resistance of the coating achieved the optimal performance when the maximum amount of hBN in the cold-sprayed Ni coating is about 6 wt%.…”
Section: Cold-sprayed Cu-based Self-lubricating Coatingsmentioning
confidence: 99%
“…Even then, the studies employing such concept are limited in the literature and involve successful depositions of W-Cu by Kang and Kang [10] and Deng et al [11], W-Ni-Fe by Xia et al [12], and low tungsten content in W-90Ta coatings by Barnett et al [13] only. Considering their excellent wear properties, a significantly broader series of studies involved the research of cemented carbides in a form of WC-Co [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], WC-Ni [32][33][34][35][36][37][38][39][40][41], WC-Co-Ni [42], WC-Co-Cr [31,[43][44][45], or WC-Cu-MoS 2 [46,47]. Unfortunately, the carbides could not be used for PFCs and so we could not built on these results.…”
Section: Introductionmentioning
confidence: 99%